Obremenjenost zraka s cvetnim prahom v letu 2023 - Kofol-Seliger, Andreja (Naše okolje, 2023)
The article presents the main characteristics of the pollen season in the year 2023. The pollen measurements were performed in the central part of the country in Ljubljana, in Izola on the Coast, in Maribor in the Štajerska region and in Lendava in the north-east of Slovenia.
Keywords: alergeni; alergije; alergijske reakcije; cvetni prah